The Relationship between Hand Therapy and Long-Term Outcomes after Distal Radius Fracture in Older Adults: Evidence from the Randomized Wrist and Radius Injury Surgical Trial. Issue 2 (August 2019) - Chung, Kevin C.; Malay, Sunitha; Shauver, Melissa J.; Chung, Kevin C.; Myra Kim, H.; Haase, Steven C.; Lawton, Jeffrey N.; Lien, John R.; Momoh, Adeyiza O.; Ozer, Kagan; Sears, Erika D.; Waljee, Jennifer F.; et al.
Abstract : Background: Older patients are frequently referred to hand therapy after distal radius fracture. Supervised therapy sessions place a transportation burden on patients and are costly on both the individual and systematic levels. Furthermore, there is little evidence that supervised therapy or home exercises improve long-term outcomes. Methods: Data were collected for the Wrist and Radius Injury Surgical Trial, a multicenter, international, pragmatic, randomized trial of distal radius fracture treatment in patients aged 60 years and older. Referral to therapy and therapy protocol were at the discretion of the treating surgeon and therapist. The authors examined outcomes between participants who underwent therapy and those who did not and assessed the duration of therapy. The authors also analyzed the effect of therapy on subgroups at risk for poor outcomes: older participants and those who had more comorbidities or lower baseline activity. Results: Eighty percent of participants underwent therapy; 70 percent participated in both supervised therapy and home exercises. Participants had a mean 9.2 supervised sessions over 14.2 weeks. There were no differences in patient-reported outcomes between participants who underwent therapy and those who did not. Participants who did not have therapy recovered more grip strength. Participants who engaged in therapy for a shorter time reported greater function, ability to work, and satisfaction. There were no relationships revealed in subgroup analyses. Conclusions: Hand therapy after distal radius fracture may not be necessary for older patients. Encouraging participants to resume activities of daily living as soon as possible may be as effective as formal therapy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II. Abstract : Evidence-Based Outcomes Article.